2010
DOI: 10.2106/jbjs.h.01086
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Compared with Traditional Transgluteal Approach for Total Hip Arthroplasty

Abstract: With regard to gait kinematics in the early postoperative period (three months), the present study showed no significant benefit for patients who underwent a total hip arthroplasty through a minimally invasive Watson-Jones approach in comparison with those who were managed with a standard transgluteal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 26 publications
2
55
0
7
Order By: Relevance
“…The area from eleven o'clock to three o'clock illustrates the initial extent of the capsulectomy for the MIS Pospischill et al found no significant differences in range of motion between a minimally invasive modified WatsonJones approach and a transgluteal approach according to Hardinge. Remarkably, the first measurements were performed ten days after surgery and the statistical power was low in this study due to the small number of 20 patients per group investigated [21]. The duration of stay in hospital, however, depends on many different patient-specific variables and can therefore only be used indirectly for comparison.…”
Section: Discussionmentioning
confidence: 96%
“…The area from eleven o'clock to three o'clock illustrates the initial extent of the capsulectomy for the MIS Pospischill et al found no significant differences in range of motion between a minimally invasive modified WatsonJones approach and a transgluteal approach according to Hardinge. Remarkably, the first measurements were performed ten days after surgery and the statistical power was low in this study due to the small number of 20 patients per group investigated [21]. The duration of stay in hospital, however, depends on many different patient-specific variables and can therefore only be used indirectly for comparison.…”
Section: Discussionmentioning
confidence: 96%
“…A number of recent studies have compared the newer approaches with traditional lateral and posterior approaches [1,12,15,18,34,49] but there is lack of consensus on whether there is any demonstrable difference in reducing muscle damage, improving postoperative gait, or facilitating earlier rehabilitation [21,29,38,41,42,46].…”
Section: Introductionmentioning
confidence: 99%
“…Recently some less invasive modifications have been described and compared to the standard approaches such as Kocher-Langenbeck (dorsal), Bauer or Hardinge (lateral), Watson-Jones (anterolateral) and Smith-Peterson (anterior). All of them seem to have several advantages and every modification leads to different new problems [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%